Ibn Al-Jazzar On Fevers A critical edition of Zad al-musafir wa-qut al-hadir - Provisions for the Traveller and Nourishment for the Sedentary, Book 7, Chapters 1-6 - Bos, Gerrit (The Sir Henry Wellcome Asian Series, 2000)
First published in 2000. Routledge is an imprint of Taylor & Francis, an informa company.